Fungus-specific SSR markers in the Antarctic lichens Usnea antarctica and U. aurantiacoatra (Parmeliaceae, Ascomycota) - Lagostina,Elisa; Dal Grande, Francesco; Ott, Sieglinde; Printzen, Christian (Applications in Plant Sciences, 2017)
PREMISE OF THE STUDY: Usnea antarctica and U. aurantiacoatra Parmeliaceae) are common lichens in the maritime Antarctic. These species share the same habitats on King George Island (South Shetland Islands, Antarctica) and are distinguishable based on reproductive strategies. METHODS AND RESULTS: We developed 23 fungus-specific simple sequence repeat (SSR) markers that cross-amplify between the two species. We used a low-coverage genome-skimming approach on one sample of each species to identify SSR repeats in the two species. Primers were designed for 3–4-bp repeats, and only the loci common to both species were selected for further analyses. Seventy-seven samples of the two species were selected to assess fungal specificity, genetic variability, and linkage of the markers. In addition, we tested cross-amplification in other Usnea species. CONCLUSIONS: The 23 newly designed SSR markers are suitable for population genetic and phylogeographic studies of Usnea species.